Buto, Ägypten: Lanschaftsarchäologie und regionale Siedlungsnetzwerke um den Fundplatz Tell el Faracin, Gouvernorat Kafr esch-Scheich - Schiestl, Robert (e-Forschungsberichte des DAI, 2023)
The regional survey around Tell el-Faracin (ancient Buto) investigates the settlement history and the changes in the landscape of this area in the northwestern Delta. Lately, the research focused on two areas: a free standing ancient settlement site, Kom el-Gir, about 4 km northeast of Buto, and fields about halfway between Buto and Kom el-Gir. At Kom el-Gir magnetic prospection revealed the plan of a settlement of the Ptolemaic and Roman periods. Auger core drillings in fields, marked as small ancient settlement sites on old maps, show no archaeological layers in this area.